Capacity of ionic liquids [EMim][NTf2] and [EMpy][NTf2] for extraction of toluene from mixtures with alkanes: Comparative study of the effect of the cation - Sandra Corderí (2012)
The ionic liquids 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, [EMim][NTf2] and1-ethyl-3-methylpyridinium bis(trifluoromethylsulfonyl)imide, [EMpy][NTf2] have been studied as solventsfor the extraction of toluene from mixtures with alkanes (heptane or cyclohexane). The liquidliquidequilibria of ternary systems {heptane or cyclohexane + toluene + [EMim][NTf2] or [EMpy][NTf2]} and{heptane + cyclohexane + [EMim][NTf2] or [EMpy][NTf2]} at 298.15K and atmospheric pressure weredetermined. The solute distribution ratio and selectivity derived from the tie-lines were used to determineif these ionic liquids can be used as extraction solvents. The tie-lines were satisfactorily correlatedby means of the thermodynamic NRTL model for ternary systems with [EMpy][NTf2] and with NRTL andUNIQUAC models for the ternary systems with [EMim][NTf2].